Microsatellite marker development for the coastal dune shrub Prunus maritima (Rosaceae)(1) - Badgley, Emily M. (Appl Plant Sci, 2015)
• Premise of the study: Microsatellite primers were developed in the beach plum, Prunus maritima, to investigate the genetic composition of remaining populations in need of conservation and, in future studies, to determine its relation to P. maritima var. gravesii. • Methods and Results: Fourteen primer pairs were identified and tested in four populations throughout the species’ geographic range. Of these 14 loci, 12 were shown to be polymorphic among a total of 60 P. maritima individuals sampled (15 individuals sampled from four populations). Among the polymorphic loci, the number of alleles ranged from two to 10 and observed heterozygosity of loci ranged from 0.07 to 0.93 among specimens tested. • Conclusions: These microsatellites will be useful in evaluating the population genetic composition of P. maritima and in developing approaches for further conservation and management of this species within the endangered coastal dune ecosystem of the northeastern United States.